From stress to psychosis: whom, how, when and why?. (6th June 2014) - Mondelli, V.
Abstract : The role of stress in precipitating the onset and relapse of psychosis has been now widely recognised. Over the past decade, the major challenge of research in this field has been to elucidate the biological mechanisms involved in the interaction between stress and psychosis onset. Obvious focus of this research has been the study of biological systems involved in the stress response. I will here briefly discuss the current evidence of abnormalities in stress biomarkers, such as cortisol and inflammatory markers, in patients with psychosis and their possible clinical implications. Stress biomarkers appear to hold strong potential as predictors of psychosis as well as of clinical outcome, and may represent optimal targets for the development of novel therapeutic agents for psychosis.